High-resolution UV and e-beam lithography for diffractive optics - Yuan, Xiaocong. (2008)
Diffractive optical elements (DOEs) are a class of optical components that are used in a diverse range of fields such as telecommunications, optical computing, consumer electronics, laser material processing and the biomedical sciences, to manipulate light through micro-optical systems. The advantages provided by DOES have made them ideally suited for such applications; they generally have less weight and occupy less volume compared to conventional optics, they may be less expensive to manufacture and can have superior optical performance. In order to get the most out of such DOEs, knowledge of the design process, fabrication, packaging in a particular system, and operation is required. These DOEs are a broad class of optical components that rely on diffraction as opposed to refraction to modify how light propagates. They manipulate the properties of an incident wave by selectively retarding portions of the wave front. This retardation is accomplished with the use of either a reflective or transmission substrate etched with the appropriate pattern required to send light in the desired direction. These patterned surfaces are made of very fine features approximately the size of the wavelength of light, hence the techniques (such as UV and Electron beam lithography) used to fabricate them have to be precise and highly controllable.